2011
DOI: 10.1111/j.1440-172x.2011.01966.x
|View full text |Cite
|
Sign up to set email alerts
|

The top eight issues Queensland Australia's aged-care nurses and assistants-in-nursing worried about outside their workplace: A qualitative snapshot

Abstract: The attainment of a work-life balance is an important issue for recruitment, retention and workforce planning. This paper aims to report on the free text data provided by the aged-care sector nurses around perceptions of important work-life issues. Data were written responses of aged-care nurses to the open-ended request at the end of a survey, which asked them to list up to five political/social/environmental issues concerning them outside of their work. For aged-care nurses, when asked to list political/soci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…Academic studies on residential aged care tend to focus on macro‐level issues (e.g., Martin & King, ; Productivity Commission, ), or on specific aspects of HRM (e.g., recruitment and retention, work‐life balance, remuneration, learning) at the organizational level (e.g., Kaine, ; Nishikawa, ; Rainbird et al, ; Rubery & Urwin, ; Tuckett et al, ; Tuckett, Hegney, Parker, Eley, & Dickie, ). In addition, empirical studies at the organizational level often focus on the nursing occupational group due to severe skill shortages within that labor segment (e.g., Arbon et al, ; Daskein, Moyle, & Creedy, ; Eley et al, ; Grealish, Bail, & Ranse, ; Tuckett et al, , ). In comparison, limited attention has been given to nonclinical staff, such as personal care workers, who make up the majority of the workforce and whose skills are also in increasingly short supply, but essential to the quality of care (Nishikawa, ; see also Gospel's study in this special issue).…”
Section: Research Agendamentioning
confidence: 99%
“…Academic studies on residential aged care tend to focus on macro‐level issues (e.g., Martin & King, ; Productivity Commission, ), or on specific aspects of HRM (e.g., recruitment and retention, work‐life balance, remuneration, learning) at the organizational level (e.g., Kaine, ; Nishikawa, ; Rainbird et al, ; Rubery & Urwin, ; Tuckett et al, ; Tuckett, Hegney, Parker, Eley, & Dickie, ). In addition, empirical studies at the organizational level often focus on the nursing occupational group due to severe skill shortages within that labor segment (e.g., Arbon et al, ; Daskein, Moyle, & Creedy, ; Eley et al, ; Grealish, Bail, & Ranse, ; Tuckett et al, , ). In comparison, limited attention has been given to nonclinical staff, such as personal care workers, who make up the majority of the workforce and whose skills are also in increasingly short supply, but essential to the quality of care (Nishikawa, ; see also Gospel's study in this special issue).…”
Section: Research Agendamentioning
confidence: 99%
“…It has been reported that nurses’ dissatisfaction with their working conditions, including shift work, is associated with their intention to leave the profession, which is a factor in workforce shortages, particularly with respect to the loss of experienced nurses (Nei, Anderson Snyder, & Litwiller, ; Rossi et al, ). These concerns about nursing shortages and the known influence of shift work on the workforce (Tahghighi et al, ; Tuckett, Hegney, Parker, Eley, & Dickie, ) highlight the need for studies to investigate the impact of working shifts on nurse psychological functioning. These phenomena are of interest to nurse leaders and policy makers, as both patient safety and the quality of nursing care patients receive are affected by absenteeism and staff turnover (International Council of Nurses, ).…”
Section: Introductionmentioning
confidence: 99%
“…, , Tuckett et al . ), highlight the need to investigate how shift work may influence nurse resilience and related psychological functioning.…”
Section: Introductionmentioning
confidence: 99%
“…As such, there is currently very little understanding of the impact of shift work on the resilience and psychological well-being of nurses. Concerns about nursing shortages and retention and previous studies into job satisfaction in the nursing workforce (Eley et al 2007, Tuckett et al 2011, highlight the need to investigate how shift work may influence nurse resilience and related psychological functioning.…”
Section: Introductionmentioning
confidence: 99%